Studi tentang Profesionalitas Guru di SMP Islam Bulurejo Tempursari Lumajang - Sholicha, Syovinatus; Ma’ani, Arifatul (MANAGIERE: Journal of Islamic Educational Management, 2023)
This study presents the professionalism of teachers. Some of the considerations that became the main reason for choosing this issue include; there are demands from society in modernization that are sweeping all aspects of people's lives, and there is differentiation and specialization that occurs among those who want an increase in every profession according to their respective fields. Bulurejo Tempursari Lumajang Islamic Middle School is an object of research based on the consideration that at that SMP there has never been any research that raises the issue of teacher professionalism. The specifics of the problem are whether the teaching staff at the Bulurejo Tempursari Lumajang Islamic Middle School can be categorized as professional teachers. Based on research data that has been analyzed by teachers at the Bulurejo Tempursari Islamic Middle School, it is not 100% that they can be categorized as professional teachers. This is because the teaching profession they carry out does not fully meet the existing aspects of teacher professionalism. However, teachers still have the desire to seek to become professionals. Several things become obstacles for them to be categorized as professional teachers, among others, there are still many of them who are not yet members of professional teacher organizations, lack independence and a future-oriented attitude, lack of facilities needed by teachers, and lack of effort to increase the professionalism of teachers and the school.